Thrombophilia, Thrombosis and Thromboprophylaxis in Pregnancy: For What and in Whom? - Middeldorp, Saskia; Naue, Christiane; Köhler, Christina (Hämostaseologie, 2022)
Compared with nonpregnant women, pregnancy carries a four- to fivefold higher risk of venous thromboembolism (VTE). Despite increasing use of heparin prophylaxis in identified high-risk patients, pulmonary embolism still is the leading cause of maternal mortality in the western world. However, evidence on optimal use of thromboprophylaxis is scarce. Thrombophilia, the hereditary or acquired tendency to develop VTE, is also thought to be associated with complications in pregnancy, such as recurrent miscarriage and preeclampsia. In this review, the current evidence on optimal thromboprophylaxis in pregnancy is discussed, focusing primarily on VTE prevention strategies but also discussing the potential to prevent recurrent pregnancy complications with heparin in pregnant women with thrombophilia.
Keywords: venous thromboembolism; thrombophilia; pregnancy complications; low-molecular-weight heparin